Inheritance of resistance to powdery mildew and agronomical performance of some oat germplasm - Herrmann, Matthias (MTT, 2004)
Powdery mildew is an endemic disease in northern parts of Germany and reduces yields depending from time and severity of infection (Bartels 1980). Resistances to powdery mildew derived from Avena macrostachya CAV5264 and A. pilosa CAV 0128 (Hoppe & Kummer 1991) have been analysed genetically using the detached-leaf tests on benzimidazole-containing agar. Segregation in F2 and BC1 are explainable by one incompletely dominant gene for resistance derived from A. macrostachya CAV5264 and one dominant gene from A. pilosa CAV 0128. Avena occidentalis CAV3889 (Herrmann & Roderick 1996), another donor for resistance to powdery mildew, was investigated in a glasshouse test with F2 and BC1F2 seedlings. According to the segregation two recessive genes encode for resistance, which will be validated by detached-leaf tests in advanced backcross generations. Several progenies derived from crosses with the resistance donors mentioned above have been examined for agronomic performance at two locations. The germplasm displayed genetic variation in yield components, whereby the lowest yields where found in progenies of crosses with A. occidentalis CAV3889, due to the low number of backcrosses (BC1) with the highyielding parent. Bartels, G., 1980. Arbeiten der DLG, 166: 79-87; Herrmann M. & H. W. Roderick 1996. Euphytica 89: 405-410; Hoppe, H.-D. & M. Kummer, M. 1991. Vortr. Pflanzenzüchtg. 20: 56 61.
Keywords: Ka; oat; Avena ssp.; resistance; powdery mildew